Efeitos relacionais no planejamento integrado de transportes - Geaquinto, Pedro Dias (2018)
Practices of transport and land use planning provide conditions for the establishment of vicious cycles of uncontrolled urban processes and historical occurrences of urban sprawl, sociospatial exclusion, and increased use of automobiles. A common reaction is to use methods that equip transit-oriented development approaches with typological analyses of the territory, in order to identify opportunities and weaknesses in the urban form. This dissertation aims to evaluate the effects of the regional relations of indicators and to introduce this assessment in the context of this kind of integrated planning. A multiple regression analysis was evaluated to verify the performance and cluster analysis was evaluated to form territorial categories. The indices selected for the Rio de Janeiro Metropolitan East were designed after their relational orders – territorial reach and scalar normalization – and classified according to their morphological or functional reference – respectively, static variables, the built environment, or dynamic variables, the transit performance. Despite a very aggregate sample, the spatial fit between the categories of clusters is reasonably discernible. In addition, the methodological constructs that produced the preparation of the study represent an important contribution – particularly, the theoretical basis on sociospatial relations, which constructed the indicators, and the network topology, which represents aspects of transit and walking in fine detail, that provided the areas that compose the territorial reach.